2016
DOI: 10.1111/papr.12502
|View full text |Cite
|
Sign up to set email alerts
|

Central Pain Processing in Patients with Shoulder Pain: A Review of the Literature

Abstract: This review has shown that great progress has been made toward a better understanding of neurophysiologic pain mechanisms in patients with shoulder pain. The presence of generalized mechanical hyperalgesia, allodynia, and impaired conditioned pain modulation in patients with MSK shoulder pain indicates the involvement of the central nervous system. Widespread somatosensory abnormalities observed in patients with HSP could suggest a central origin for their shoulder pain and predispose patients with HSP to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 51 publications
(225 reference statements)
0
62
1
4
Order By: Relevance
“…Also, there is an imbalance observed between the inhibitory and facilitatory pathways, which in turn implies that central sensitization involves alteration in the sensory processing of the brain (Staud et al , 2007 ). Negative pain perception hinders the healing process and leads to cognitive behavioral changes in the individual (Noten et al ., 2017 ). The psychological and social factors play a mediating role between impairments and perceived disability by an individual (Lindenhovius, Buijze, Kloen, & Ring, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is an imbalance observed between the inhibitory and facilitatory pathways, which in turn implies that central sensitization involves alteration in the sensory processing of the brain (Staud et al , 2007 ). Negative pain perception hinders the healing process and leads to cognitive behavioral changes in the individual (Noten et al ., 2017 ). The psychological and social factors play a mediating role between impairments and perceived disability by an individual (Lindenhovius, Buijze, Kloen, & Ring, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Temporal summation of pain (TSP) and conditioned pain modulation (CPM) have been used to assess central pain gain and impaired pain inhibition in musculoskeletal pain conditions 10 . Enhanced TSP and/or impaired CPM have been shown in chronic pain conditions, such as osteoarthritis 11,12 , fibromyalgia 13 , whiplash-associated disorders 14 , shoulder pain 15 , and in computer users with high NSP intensity 8 . There is promising evidence suggesting that measures of central pain modulation may be prognostic factors to predict the outcome after e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some autors have suggested an involvement of central pain mechanisms secondary to continuous nociception characteristic of the early stages of FS [6]. Two systematic reviews showed preliminary evidence that central pain mechanisms may contribute to shoulder pain of different etiologies [7,8], but other studies questioned those ndings [9]. Importantly, these reviews did not included people with FS, so the role of the central nervous system (CNS) in FS remains speculative.…”
Section: Introductionmentioning
confidence: 99%